Happiness at work in small and medium-sized enterprises: an analysis of innovation and creativity - Orlando Josué Martínez-Arvizu; Mario Alberto Salazar-Altamirano; Esthela Galván-Vela; Rosa Anaya-Aguilar; Carmen Anaya-Aguilar (BMC Psychology)
Abstract Background This study focuses on analysing the relationship between digital innovation, innovation culture, creativity, and happiness at work in the context of small and medium-sized enterprises (SMEs) in Mexico. As digitalisation transforms work processes, it becomes essential to understand how these factors interact and impact employee well-being, especially in emerging economies. Methods The research adopted a non-experimental quantitative approach using a cross-sectional design. A multigroup analysis was applied through Structural Equation Modelling (SEM) to examine the relationships between variables in two groups of companies (small and medium-sized). The sample included 208 workers from various sectors in Mexico. Likert scale questionnaires, based on validated instruments, were used to measure digital innovation, innovation culture, creativity, and happiness at work. Results The results revealed that digital innovation positively impacts employee creativity, especially in small companies (β = 0.140, p < 0.10), where more flexible structures allow greater autonomy. However, in medium-sized companies, the effect of digital innovation on happiness at work largely depends on an innovation culture (β = 0.533, p < 0.001) that promotes experimentation and collaboration. Creativity has a positive and significant effect on happiness at work (β = 0.447, p < 0.001), highlighting the importance of an organisational environment that values creativity. The model explained 67.2% of the variance in happiness at work, emphasising the crucial role of these variables in enhancing employee well-being. Conclusions The study confirms that the synergy between digital innovation, innovation culture, and creativity is crucial for fostering happiness at work, although the effect varies depending on company size. In small companies, organisational flexibility facilitates the direct effect of digitalisation on creativity and happiness at work. However, in medium-sized companies, a stronger focus on innovation culture is required to maximise these benefits. These findings suggest the need for differentiated strategies to promote organisational well-being across companies of different sizes.